Structural and magnetic properties of chemically synthesized yttrium-substituted nickel nanoferrite - Atefeh Azizi Moghaddam; Abdol Mahmood Davarpanah (Journal of Particle Science and Technology, 2022)
In this paper, yttrium-substituted nickel ferrite (NiY2xFe2-2xO4) nanostructures were synthesized via the co-precipitation method with different concentrations of yttrium (x = 0.00, 0.02, 0.06, and 0.12 %, where x is the dopant concentration in molar percent) after calcination at 500 ºC. Structural studies of the samples were analyzed using X-ray diffractometry (XRD) technique. XRD results showed that the addition of Y led to an increase in synthesized nanoparticles. Molecular studies have been done using Fourier transform infrared (FT-IR) spectroscopy. FT-IR results showed that the bands at about 550-560 and 433 cm-1 are associated with tetrahedral and octahedral Metal-O bonds, respectively. Field emission scanning electron microscopy (FE-SEM) exhibit that adding  Y3+ ions dopant up to x = 0.06 led to a considerable decrease in the powders’ particle size. Adding more dopant up to x = 0.12 led to an amorphous and crystalline phase formation. The size of nanoparticles before substitution estimated from FE-SEM images were 39.49, 36.49, and 50.78 nm, which increased to 63.07, 64.02, and 73.56 nm after the substitution, respectively. The magnetic behavior of the samples was investigated using vibrating sample magnetometry (VSM) at room temperature (RT). VSM results showed that the saturation magnetization and coercivity (Hc) values decreased with the increase of yttrium contents up to x = 0.12. This was referred to as the redistribution of cations on the octahedral bonds.